Submerged Shoal Imaging By Sub-Bottom Profiler TechniqueSouthern Iraq/ Northwest of the Arabian Gulf - Majeed, Al-Mosawi; Al-Rawi, Fitian; Almayahi, Ali (Iraqi Journal of Science, 2025)
A marine geophysical survey using high-resolution Sub Bottom Profiler wascarried out for Palinurus Shoal (PS) , one of the shallow sites within Iraqi marineborders, NW of the Arabian Gulf. Eight parallel transverses survey lines of (SBP)were performed at the study area from southwest to northeast. Six lines were about2.5 km in length, the two more lines crossed about 4.6 km area extended up toKhawr Al Khafga. The distance separated the survey lines is about 0.6-0.8 km. Inaddition, one more profiler was acquired longitudinal to the north-south direction,6.3 km length. Abrupt reflectors slope changes reflectors discontinuity andcoherency were the main interpretation guides on the sub-bottom images. Thebehavior of the built-surface articulates that Palinurus Shoal feature was formed bystructural activity of a deeper diapiric structure. The surface depth is fluctuated. Itwas 6-7 m at the center of the structure and deepen toward the east to be 13-14 m.And it becomes even deeper, up to 30 m, at the western end. The dimension of theobserved structure surface are about 6 km along northwest-southeast direction andabout 2-2.5 km along transvers direction. Toward the east of the observed diapiric,there is an evidence of another daipriric structure. These structural features,diapirics, suggest the evolution of salt plugs from a salt accumulations (e.g., saltdomes or pillow structures). This postulate was proved by reflection disappearancethrough these bodies. It is characteristics of seismic waves behavior at saltcompositions. Furthermore, tilt reflectors faults and distortions of the structurebottom may tie-in neotectonic activity in the region.